(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article explores the role of green finance and web-based tools in achieving sustainable development goals. The primary focus is on assessing the energy efficiency of buildings and infrastructure. The paper analyzes modern digital platforms (e.g., Eco Green Building Standard, NYSERDA, Green Algorithms), which provide investors and developers with the ability to accurately assess the environmental sustainability of projects and effectively minimize their carbon footprint.